(3GdSLd Gdefgi ajg Yf GdNeQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg GdPi CYR GdESdGe HChdjGFg GdeJbjf hNU MOhOg def ESJMaXg ef CFeI Ojfg s
(3BNQgG (B:s
(3aEf CejQ GdeDefjf bO MXQ Pdc LedI hCNHQg hfgi Yf GdecQ hGdMeO ddg hMOg hUdhGJg Ydi QShdg NGJe GdfHjjf hBdg GdWGgQjf hSdGeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi MhGTi GdfSNI JaSjQGJ dHYV YHGQGJ GdeJf ecJhHg HGdbde GdCMeQs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds